Burnout Profiles Among Young Researchers: A Latent Profile Analysis - Boone, Anke; Vander Elst, Tinne; Vandenbroeck, Sofie; Godderis, Lode (Frontiers in Psychology, 2022)
Introduction. Burnout is a growing problem among young researchers, affecting individuals, organisations and society. Our study aims to identify burnout profiles and highlight the corresponding job demands and resources, resulting in recommendations to reduce burnout risk in the academic context. Methods. This cross-sectional study collected data from young researchers (n=1123) at five Flemish universities through an online survey measuring burnout risk, work engagement, sleeping behaviour, and the most prominent job demands (e.g. publication pressure) and resources (e.g. social support). We conducted Latent Profile Analysis (LPA) to identify burnout profiles in young researchers, and subsequently compared these groups on job demands and resources patterns. Results. Five burnout profiles were identified: (1) High Burnout Risk (9.3%), (2) Cynical (30.1%), (3) Overextended (2.3%), (4) Low Burnout Risk (34.8%), and (5) No Burnout Risk (23.6%). Each burnout profile was associated with a different pattern of job demands and resources. For instance, high levels of meaningfulness (OR = -1.96) decreased the odds to being classified in the Cynical profile. Conclusions. Our findings show that the Cynical profile corresponds to a relatively high number of young researchers, which may imply that they are particularly vulnerable to the cynicism dimension of burnout. Additionally, work-life interference and perceived publication pressure seemed the most significant predictors of burnout risk, while meaningfulness, social support from supervisor and learning opportunities played an important protective role.